The struggle of EFL students in thesis writing: Investigating language challenges and the role AI in academic writing assistance - Ninuk Indrayani; Febrina Rizky Agustina (Universitas Islam Negeri (UIN) Syekh Wasil, Kediri, Indonesia, 2026)
Thesis writing is a crucial milestone for undergraduates, yet English as a Foreign Language (EFL) learners enrolled in the English Language Teaching (ELT) program continue to struggle with academic writing despite nearly four years of English instruction. This study investigates the persistent challenges faced by EFL students in writing their theses, particularly in language-related issues. Additionally, it explores the role of artificial intelligence (AI) tools in assisting students during the thesis writing and revision process. Using a qualitative approach, 7 EFL students from an ELT program were interviewed, and the data were analyzed using thematic analysis to explore their language-related challenges in thesis writing as well as their perceptions and use of AI-assisted writing tools. Findings reveal that the students encountered significant challenges in grammar mastery, academic vocabulary, adherence to academic writing conventions, and L1 interference. These issues often pushed students to rely heavily on AI tools such as for paraphrasing, grammar correction, translation, and academic adjustment. While there were benefits, the students also reported drawbacks, for example, technical limitations, stylistic mismatches, misalignment, and reduced independence in writing. Whereas AI improved the surface quality of student writing, it simultaneously undermined authenticity and critical engagement, particularly when EFL students relied on AI for paraphrasing, translation, and expanding literature review sections. The findings highlight the urgent need for embedded-AI literacy integration into ELT curricula to equip students with the skills required to navigate technological assistance in developing independent, critical, and authentic writing competence.